Seasonal differences in biochemical parameters of bone remodelling. - Douglas, A S (1996)
AIMS: To compare bone remodelling parameters in late autumn and early spring in 20 post-menopausal women. METHODS: The parameters measured were serum osteocalcin and its apparent degree of carboxylation (measured by hydroxyapatite binding), total and bone specific alkaline phosphatase and urinary bone resorption markers, (pyridinoline and deoxypyridinoline). RESULTS: Serum osteocalcin concentrations were lower in autumn than in spring but the degree of carboxylation was similar. Total and bone specific alkaline phosphatase activities in serum were higher in autumn than in spring. These results support previous observations. However, notable and previously unreported changes in urinary bone resorption markers were observed. Pyridinoline concentrations were lower and deoxypyridinoline higher in autumn compared with spring. The ratio of pyridinoline:deoxypyridinoline was therefore very different between the seasons. CONCLUSIONS: The results clearly demonstrate that seasonal changes in these variables of bone remodelling must be taken into consideration when designing, reporting or analysing studies of bone metabolism in vivo.